2010
DOI: 10.1111/j.1476-5381.2010.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

The quantal secretion of catecholamines is impaired by the accumulation of β‐adrenoceptor antagonists into chromaffin cell vesicles

Abstract: Background and purpose: The delayed onset of certain effects of antagonists of b-adrenoceptors (b-blockers), such as lowering arterial blood pressure (several days), cannot be explained solely by their effects on b-adrenoceptors, an action that occurs within minutes. Although several mechanisms have been proposed, none of them explain this temporal delay. This work aimed at providing a new explanation based on the interference of these drugs with the functional accumulation of catecholamines within neurosecret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Hydralazine and some beta-blockers have been reported to accumulate in secretory vesicles of chromaffin cells and thereby displace catecholamines leading to reduced vesicular content and altered release kinetics 39,40 . Therefore, to assess these possibilities and gain more precise mechanistic insight we used carbon fiber amperometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydralazine and some beta-blockers have been reported to accumulate in secretory vesicles of chromaffin cells and thereby displace catecholamines leading to reduced vesicular content and altered release kinetics 39,40 . Therefore, to assess these possibilities and gain more precise mechanistic insight we used carbon fiber amperometry.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work demonstrated that second messenger pathways can alter the content and/or emptying of secretory vesicles upon stimulation 48–53 . Furthermore, hydralazine and β blockers can accumulate in secretory vesicles and thereby reduce the amount and kinetics of catecholamine release from each vesicle 39,40 . Using carbon fiber amperometry we show that gabapentin reduced the number of vesicles that undergo exocytosis, but did not change the amount or kinetics of catecholamine released from these unitary events (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we also showed that the accumulation of β-Bs like atenolol, labetalol and propranolol (false neurotransmitters) has a significant effect on the quantum release of adrenaline [3]. Likewise, we demonstrated that the β-B labetalol was co-liberated with catecholamines.…”
Section: Resultsmentioning
confidence: 65%
“…104 Similarly, it has been reported that beta-blockers can accumulate into the vesicles of bovine chromaffin cells, thus decreasing the concentration of released catecholamines and inducing a decrease in sympathetic tone. 105 This result could explain, in part, the delay in the hypotensive effect of beta-blockers.…”
Section: Electrochemical Methods At Single Cellsmentioning
confidence: 99%